Effect of Different Beehives Size and Daily Activity of Stingless Bee Tetragonula Laeviceps on Bee-Pollen Production - Ali Agus; Agussalim Agussalim; Nafiatul Umami; I Gede Suparta Budisatria (Faculty of Animal Science, Universitas Gadjah Mada, 2019)
Bee activities and colony may affect the production of bee products. Bee-pollen is one of the important products of honeybees, besides of honey. Tetragonula laeviceps is a group member of stingless bees found in tropical region. In Indonesia, Tetragonula laeviceps mostly create a nest in bamboos that make unfortunately difficult for harvesting of its products. The aim of this study was to investigate the effect of different beehives size and the daily activity (morning vs. afternoon) of stingless bee Tetragonula laeviceps on bee-pollen production. This study was conducted in Ngrandu, Katongan Village, Sub-district of Nglipar, Gunungkidul, Yogyakarta. Forty colonies of Tetragonula laeviceps were obtained from bamboos (similar in diameter and length) were transferred into four different group of beehives size (BS) made from dried wood, respectively: 35x17.5x13.5 (BS1); 35x20x17.5 (BS2); 37.5x20x20 (BS3) and 40x20x20 cm (BS4). Each group of beehives size had ten colonies/beehives as replicates. The colonies consisted of a queen bee, eggs, worker bees, and drones were transferred into wood beehives, and they were kept for two months for the study. The bee-pollen was harvested from beehives, separated from the propolis then weighed. The production of bee-pollen in the four different beehives size (BS1: 2.34±2.48 g/colony; BS2: 4.56±3.94 g/colony; BS3: 1.30±1.22 g/colony, BS4: 1.02±0.63 g/colony) was not different (ns) among the groups. The daily activity of bee bring the pollen to the nest in the morning (07.00 to 11.00) was significantly different (P<0.05) among the groups, but not significant (ns) different in the afternoon (14.00 to 17.00). The frequency of bringing in pollen into the hives at the morning is higher than at the afternoon (21.75 vs. 12.43 times/5 minutes). It could be concluded that the colony in beehive size of BS2 (35x20x17.5 cm) has higher daily activities and thus higher bee-pollen production, compared to the other beehives groups.